Molecular Mechanisms of Isolated Polycystic Liver Diseases - Yu, Ziqi; Shen, Xiang; Hu, Chong; Zeng, Jun; Wang, Aiyao; Chen, Jianyong (Frontiers in Genetics, 2022)
Polycystic liver disease (PLD) is a rare autosomal dominant disorder including two genetically and clinically distinct form, autosomal dominant polycystic kidney disease (ADPKD) and isolated polycystic liver disease (PCLD). The main manifestation of ADPKD is kidney cysts, while PCLD has predominantly liver presentations with mild or absent kidney cysts. Over the past decade, PRKCSH, SEC63, ALG8 and LRP5 have been found as the candidate genes of PCLD. Recently, more candidate genes such as GANAB, SEC61B and ALR9 were also reported in PCLD patients. In this review, we focused on all candidate genes of PCLD including the newly established novel candidate genes. In addition, we also discussed some other genes which might also contribute to the disease.